Digital Banks in Indonesia: Potential and Problems - Ronald Fadly Sopamena; Lastuti Abubakar; Tri Handayani (Batulis Civil Law Review)
Introduction: Digital Bank based on POJK No.12/POJK.03/2021 Concerning Commercial Banks, is a bank incorporated in Indonesia that provides and carries out business activities mainly through electronic channels without a physical office other than the head office or using limited physical offices. Digital banks are then explained in Article 7B and Article 20A of the PPSK Law stating that both commercial banks and Islamic commercial banks can operate as digital banks. Based on this, the business fields of digital banks are the same as the business fields of commercial banks or Islamic commercial banks. Digital banks are divided into digital banks that are subsidiaries of conventional banks and banks that have been purely digital banks since their inception.